2020
DOI: 10.1037/cfp0000138
|View full text |Cite
|
Sign up to set email alerts
|

College students’ motivations for “hooking up”: Similarities and differences in motives by gender and partner type.

Abstract: Using a sample of 348 single, primarily heterosexual university students with a recent (i.e., past 10-week) hook-up experience, we examined motivations for hooking up at both a global-and event level (i.e., motivations for hook ups in general and for the participants' most recent hook up). We also tested for differences in motivations for hooking up by gender and type of partner (i.e., stranger, acquaintance, friend, exromantic partner). Contrary to popular notions of hook ups as one-time sexual encounters voi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 81 publications
(177 reference statements)
0
20
0
Order By: Relevance
“…A third study investigated how six motivations (relationship desire, lack of dating scene, sexual gratification, wanting to fit in, fun/excitement, and not enough time to pursue a relationship) grouped together to create four distinct classes of hookup motivations including Utilitarians (motivated by hookup enjoyment but use hookups as a catalyst into relationships due to a weak dating scene), Uninhibiteds (motivated by fun and sexual gratification), Unispireds (are not strongly motivated by anything), and Unreflectives (are neutral on all hookup motivations) (Uecker et al 2015 ). Weitbrecht and Whitton ( 2020 ) examined motivations for college hookups, finding the most common were physical pleasure, followed by feeling attractive, substance use, romantic relationship formation, lack of long term commitments, sexual experimentation, and gaining sexual experience. Less common motivations included loneliness, increasing social status, peer pressure, or because other people were doing it.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…A third study investigated how six motivations (relationship desire, lack of dating scene, sexual gratification, wanting to fit in, fun/excitement, and not enough time to pursue a relationship) grouped together to create four distinct classes of hookup motivations including Utilitarians (motivated by hookup enjoyment but use hookups as a catalyst into relationships due to a weak dating scene), Uninhibiteds (motivated by fun and sexual gratification), Unispireds (are not strongly motivated by anything), and Unreflectives (are neutral on all hookup motivations) (Uecker et al 2015 ). Weitbrecht and Whitton ( 2020 ) examined motivations for college hookups, finding the most common were physical pleasure, followed by feeling attractive, substance use, romantic relationship formation, lack of long term commitments, sexual experimentation, and gaining sexual experience. Less common motivations included loneliness, increasing social status, peer pressure, or because other people were doing it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Women typically experience more negative consequences for engaging in hookups while men receive more positive reinforcement (Allison and Risman 2013 ; Hamilton and Armstrong 2009 ; Reiber and Garcia 2010 ). Past research has found women are more likely to endorse motives for sex and hookups such as love, commitment, initiating or solidifying an enduring relationship, and being compliant to their partner, compared to men (Bogle 2008 ; Hatfield et al 2010 ; Weitbrecht and Whitton 2020 ). Women who wish they had more opportunities to form long term relationships are also more likely to have hooked up in the past; although it is unclear if this desire to form relationships preceded or were a result of that hookup experience (Kuperberg and Padgett 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations